2012
DOI: 10.1186/1471-2458-12-109
|View full text |Cite
|
Sign up to set email alerts
|

Research, evidence and policymaking: the perspectives of policy actors on improving uptake of evidence in health policy development and implementation in Uganda

Abstract: BackgroundUse of evidence in health policymaking plays an important role, especially in resource-constrained settings where informed decisions on resource allocation are paramount. Several knowledge translation (KT) models have been developed, but few have been applied to health policymaking in low income countries. If KT models are expected to explain evidence uptake and implementation, or lack of it, they must be contextualized and take into account the specificity of low income countries for example, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
149
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(153 citation statements)
references
References 36 publications
2
149
0
2
Order By: Relevance
“…Several studies have identified lack of training in EBPH as a major hindrance to incorporating evidence into health decisions and interventions in LMICs (Nagpal, Sinclair & Garner 2013;Oliver et al, 2014). For instance, a study by Orem et al (2012) in Uganda which explored the perspectives of policy actors on improving the uptake of evidence in health policy development and implementation identified capacity building in evidence-based practice as key to improving the use of evidence in decision-making. Armstrong et al's (2014) study conducted among Australian local public health managers also revealed that managers who had received training in EBPH had increased level of confidence in searching, assessing quality and combing various sources of evidence to aid decision-making.…”
Section: Barriers To Ebph Implementationmentioning
confidence: 99%
“…Several studies have identified lack of training in EBPH as a major hindrance to incorporating evidence into health decisions and interventions in LMICs (Nagpal, Sinclair & Garner 2013;Oliver et al, 2014). For instance, a study by Orem et al (2012) in Uganda which explored the perspectives of policy actors on improving the uptake of evidence in health policy development and implementation identified capacity building in evidence-based practice as key to improving the use of evidence in decision-making. Armstrong et al's (2014) study conducted among Australian local public health managers also revealed that managers who had received training in EBPH had increased level of confidence in searching, assessing quality and combing various sources of evidence to aid decision-making.…”
Section: Barriers To Ebph Implementationmentioning
confidence: 99%
“…KT platforms), and supportive policy structures for implementation of research evidence (plans, guidelines, monitoring frameworks) (6). These are crucial as they can potentially offset the consequences of the high turnover in government related to leakage of capacity, discontinued relationships and shuffled priorities.…”
Section: Capacity Building Componentsmentioning
confidence: 99%
“…inadequate food safety laws and weak governance) and prioritize research areas and review questions. Establishing a sustained partnership with all relevant stakeholders that spans the entire process from setting the research agenda to implementation, increases the acceptability of the evidence among stakeholders, which in turn, promotes its uptake and use in policy-making (6,11,14). Although the role of civil societies and community representatives remains largely unexplored (15), involving the latter two groups is important in light of the increasing push for people-centred care and people-centred health systems.…”
Section: Capacity Building Componentsmentioning
confidence: 99%
See 2 more Smart Citations